Validation of RNA extraction procedures focused on micro RNA expression analysis - Remáková, M; Škoda, M; Faustová, M; Vencovský, J; Novota, P (Folia biologica, 2013)
The sampling procedure is a crucial step in every kind of experiment. This is also true in gene expression profiling experiments, where high quality and sufficient quantity of extracted RNA plays a significant role in the experimental outcome. We have compared five different RNA extraction protocols from peripheral blood/PBMCs with the aim to define the most suitable method for the miRNA expression profiling experiments. Convincing results in terms of highest quantity and quality were obtained by the TRIzol-chloroform extraction method. The total RNA obtained using this method contained the highest portion of good-quality miRNA molecules, which was also confirmed by gene-specific real-time PCR experiments.
Keywords: Reproducibility of Results; Gene Expression Regulation; mikro RNA; Gene Expression Profiling; reprodukovatelnost výsledků; MicroRNAs; Humans; Animals; lidé; stanovení celkové genové exprese; Molecular Biology; zvířata; regulace genové exprese; molekulární biologie